Mineralogical and geochemical characteristics of the third member of Palaeogene Dongying formation in the Nanpu Sag, Bohai Bay Basin: implications for controlling on organic matter accumulation - Yin, Shiyan; Yao, Aidong; Cheng, Jianzhong; Lei, Chuang; Wang, Zhaosheng; Zhang, Zhenguo; Zhang, Ying; Wang, Yu; Han, Xiaoying; Ma, Zhigang (Frontiers in Earth Science, 2025)
Introduction and MethodsTo identify the unconventional shale oil exploration potential of the third member of the Palaeogene Dongying Formation (Ed3) in the Nanpu Sag, Bohai Bay Basin, variations in paleoclimate and paleoenvironment and their influence on organic matter accumulation were investigated through analyzing mineralogical and geochemical characteristics of forty-nine mudstone samples.ResultsResults show that the Ed3 mudstones exhibit strong heterogeneity with the organic carbon content ranging from 0.30% to 2.66%, petroleum potential yield ranging from 0.44 to 11.41 mg/g, and hydrogen index ranging from 57 to 466 mg/g TOC, which are dominated by mixed kerogen and low maturity to maturity. Multiple mineralogical and geochemical proxies suggest that the semi-humid to semi-arid paleoclimate during the Ed3 period governed the fluctuations of paleoenvironmental elements. From bottom to top, the paleowater depth varied in an order of shallow water, deep water, and shallow water, respectively, and the corresponding paleosalinity of brackish water, fresh water, and brackish waterr, respectively. Water column evolved from weak oxidation to weak reduction, and then to weak oxidation, respectively. Two development models of the Ed3 mudstones under semi-humid to humid and semi-arid to arid climate were summarized based on the influence of paleoenvironmental elements on organic matter supply and preservation/degradation in sediments. Mudstones were deposited in a deep-water environment with high primary productivity under the semi-humid to humid climate. The mixed aquatic and terrigenous organic matte were efficiently preserved in stratified and reduced water columns, resulting in high organic matter accumulation. Nevertheless, mudstones were developed in a shallow-water environment with medium primary productivity under the semi-arid to arid climate. Here, aquatic organic matter was oxidized and degraded in the oxidation condition, leading to low organic matter accumulation.DiscussionThe exploration of unconventional shale oil in the Ed3 member of Nanpu Sag should focus on the organic-matter-rich mudstones developed in the humid climate.